Stride length regulation at the approach phase of long jump in visually impaired (F12 class) athletes - Theodorou, A.; Emmanouil, S.; Sotiris, P.; Tasoulas, E.; Panoutsakopoulos, V.; Josep, P. -R.; Miguel, T. -J.; Panteli, F. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The present study examined whether long jumpers with visual impairment (class F12) demonstrate at the approach run the same pattern of footfall variability across trials as athletes without visual impairment. Five male and five female elite F12 class long jumpers were recorded during a competition. The athletes demonstrated an initial ascending footfall variability followed by a descending one, suggesting the existence of stride length regulation. This regulation emerged on the fourth and the third stride prior to take-off area and at a mean distance of 9.09 ± 0.26 m and 6.28 ± 0.26 m for the males and the females respectively from the take-off line. Results indicated that the stride pattern of F12 class long jumpers was similar to that reported in the literature for athletes without visual impairment, with stride regulation commencing one stride closer to the take-off board.